PENERAPAN MEDIA PEMBELAJARAN WORDWALL UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS V SDN 106831 BAKARAN BATU T.A 2024/2025 - Chepbriandi Munthe; Sutikno, S.Pd, M.Pd, Ph.D; Asnarni Lubis, S.Pd., M.Pd; Aimi Marlinda (STKIP Subang, 2025)
This classroom action research was conducted on fifth grade students of SDN 106831 Bakaran Batu. This research was motivated by the problem of low student learning activity during the learning of Natural and Social Sciences (IPAS) subjects. The main objective of this study was to improve student learning activity in IPAS lessons through the application of Wordwall media. The subjects of the study were 23 fifth grade students of SDN 106831 Bakaran Batu. The research process was carried out in two cycles with stages of planning, implementation of actions, observation, and reflection in each cycle. During the observation stage, the researcher used an observation sheet of learning activity to monitor the level of student involvement in learning. Initial data or pre-cycle showed that the level of student learning activity was still relatively low with an average of 57.18%. After the application of Wordwall media in the first cycle, there was an increase in activity to 69.57%, which showed an increase towards the fairly good category. Furthermore, in the second cycle, there was a significant increase to 90.11%, which was in the very good category. Thus, the use of Wordwall media has proven effective in increasing students' learning activity in the subject of science for grade V.Keywords: Wordwall media, Student learning activity, Classroom action research, Science learning for grade V.